Historical evolution and present status of family medicine in Sri Lanka - R. P. J. C. Ramanayake (Journal of Family Medicine and Primary Care, 2013)
Sri Lankan health system consists of Allopathic, Ayurvedic, Unani, and several other systems of medicine and allopathic medicine is catering to the majority of the health needs of the people. As in many other countries, Sri Lankan health system consists of both the state and the private sector General practitioners, MOs in OPDs of hospitals and MOs of central dispensaries, provide primary medical care in Sri Lanka. Most of the general practices are solo practices. One does not need postgraduate qualification or training in general practice to start a general practice. There is no registered population for any particular health care institution in the state sector or in the private sector and there is no strict referral procedure from primary care to secondary or tertiary care. Family doctors have been practicing in Sri Lanka for well over 150 years. The first national organization of general practitioners was Independent Medical Practitioner (IMPA)′s organization which was founded in 1929 and the College of General Practitioners of Sri Lanka was founded in 1974. College conducts its own Membership Course and Examination (MCGP) since 1999. Family Medicine was introduced to undergraduate curriculum in Sri Lanka in early 1980s and now almost all the medical faculties in the country have included Family Medicine in their curricula. In 1979, General Practice/Family Medicine was recognized as a specialty in Sri Lanka by the postgraduate institute of Medicine. Diploma in Family Medicine (DFM) and MD Family Medicine are the pathways for postgraduate training in Sri Lanka. At present 50 to 60 doctors enroll for DFM every year and the country has about 20 specialists (with MD) in Family Medicine. The author′s vision for the future is that all the primary care doctors to have a postgraduate qualification in Family Medicine either DFM, MD, or MCGP which is a far cry from the present status.